Augmented knowledge of results feedback in tennis serve training - Moran, K.; Murphy, C.; Cahill, G.; Marshall, B. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to determine if augmented knowledge of results (KR) feedback, in the form of service speed, could enhance service speed after a six week training period. Twelve national standard junior tennis players completed six weeks of dedicated service training, three times per week; each training session consisted of 90 serves. Six players received augmented KR feedback and six did not. A Wilcoxon signed-rank test was used to compare pre- vs post- intervention results, and a Mann-Whitney test was used to examine if the differences between these results were larger in one of the groups (? = 0.05). Results showed that both the augmented KR feedback group and the no feedback group significantly improved (0.8±0.4 m.s-1 vs 0.2±0.1 m.s-1, respectively), but that the improvement was significantly larger for the augmented KR feedback group. These results suggest that it is beneficial to utilize augmented KR feedback, in the form of service speed, when undertaking a six weeks training program with elite tennis players.